(untitled) (Baghdad Science Journal, 2024)
Beta thalassemia is one of the most common hereditary diseases in the world caused by a deficiency of globin chains. Heart disease is one of the main complications of this disease as a result of excess iron deposition in the cardiac tissues. Total of 100 patients of 2-18 years diagnosed with ß-TM were employed in the current study and admitted to Thi-Qar Center of Hereditary Blood Diseases in Thi-Qar city, Iraq, and 80 healthy participants, matched by age, and geographical area were adopted as control group. The current study included evaluating of serum Troponin I (c.TnI), Creatine kinase-MB isoenzyme (CK-MB), Apelin, aspartate aminotransferase (AST), and Lactate Dehydrogenase enzyme (LDH) of studied groups. The finding revealed a significant increase (p<0.01) of c.TnI, CK-MB, AST, and LDH levels as well as a significant decrease (p<0.01) in apelin level in all patients with ß-TM compared to the control group. Pearson’s correlation coefficient (r) was also found between the biochemical parameters studied for ß-TM patients with ferritin level, were found a significant correlation (p<0.01) between ferritin level with CK-MB, LDH, and AST levels while there was no significant correlation (P>0.01) through apelin and c.TnI levels. The finding showed a clinical predictor to damage cardiac tissues in the near term, which portends the use of more efficient treatment protocols to remove excess iron from ß-TM patients.